Catalysis of Na⁺ permeation in the bacterial sodium channel NaVAb - Chakrabarti, Nilmadhab; Ing, Christopher; Payandeh, Jian; Zheng, Ning; Catterall, William A.; Pomès, Régis (Proceedings of the National Academy of Sciences - PNAS, 2013)
Determination of a high-resolution 3D structure of voltage-gated sodium channel Na VAb opens the way to elucidating the mechanism of ion conductance and selectivity. To examine permeation of Na ⁺ through the selectivity filter of the channel, we performed large-scale molecular dynamics simulations of Na VAb in an explicit, hydrated lipid bilayer at 0 mV in 150 mM NaCl, for a total simulation time of 21.6 μs. Although the cytoplasmic end of the pore is closed, reversible influx and efflux of Na ⁺ through the selectivity filter occurred spontaneously during simulations, leading to equilibrium movement of Na ⁺ between the extracellular medium and the central cavity of the channel. Analysis of Na ⁺ dynamics reveals a knock-on mechanism of ion permeation characterized by alternating occupancy of the channel by 2 and 3 Na ⁺ ions, with a computed rate of translocation of (6 ± 1) × 10 ⁶ ions⋅s ⁻¹ that is consistent with expectations from electrophysiological studies. The binding of Na ⁺ is intimately coupled to conformational isomerization of the four E177 side chains lining the extracellular end of the selectivity filter. The reciprocal coordination of variable numbers of Na ⁺ ions and carboxylate groups leads to their condensation into ionic clusters of variable charge and spatial arrangement. Structural fluctuations of these ionic clusters result in a myriad of ion binding modes and foster a highly degenerate, liquid-like energy landscape propitious to Na ⁺ diffusion. By stabilizing multiple ionic occupancy states while helping Na ⁺ ions diffuse within the selectivity filter, the conformational flexibility of E177 side chains underpins the knock-on mechanism of Na ⁺ permeation.